Antagonizing Effects of Clematis apiifolia DC. Extract against Benzo[a]pyrene-Induced Damage to Human Keratinocytes. (5th November 2019) - Lee, Seung Eun; Park, See-Hyoung; Yoo, Ju Ah; Kwon, Kitae; Kim, Ji Woong; Oh, Sae Woong; Park, Se Jung; Kim, Jangsoon; Yu, Eunbi; Han, Byung Seok; Cho, Jae Youl; Lee, Jongsung
Abstract : Background . Benzo[a]pyrene (B[a]P), a polycyclic aromatic hydrocarbon present in the atmosphere, has cytotoxic and carcinogenic effects. There have been no reports to demonstrate involvement of Clematis apiifolia DC. extract (CAE) in B[a]P-induced effects. This study was conducted to investigate the effect of CAE on B[a]P-induced effects and to elucidate its mechanism of action in HaCaT human keratinocytes. CAE inhibited aryl hydrocarbon receptor (AhR) signaling by decreasing both XRE reporter activity and expression of cytochrome P450 1A1 (CYP1A1) induced by B[a]P treatment in HaCaT cells. We also found that B[a]P-induced nuclear translocation of AhR and production of reactive oxygen species (ROS) and proinflammatory cytokines were attenuated by CAE treatment. CAE treatment suppressed B[a]P-induced phosphorylation of Src (Tyr416). In addition, dasatinib, a Src inhibitor, also inhibited B[a]P-induced nuclear translocation of AhR, similar to CAE treatment. In addition, CAE activated antioxidant response element (ARE) signaling by increasing ARE luciferase reporter activity and expression of ARE-dependent genes such as nuclear factor (erythroid-derived 2)-like 2 (Nrf2), NAD(P)H dehydrogenase [quinone] 1 (NQO1), and heme oxygenase-1 (HO-1). Nuclear translocation of Nrf2 by CAE was demonstrated by Western blot analysis and immunocytochemistry. The effects of CAE on ARE signaling were attenuated by knockdown of the Nrf2 gene. Inhibition of AhR signaling and activation of antioxidant activity by CAE operated in a reciprocally independent manner as evidenced by AhR and Nrf2 siRNA experiments. These findings indicate that CAE exerts protective effects against B[a]P by inhibiting AhR signaling and activating Nrf2-mediated signaling, suggesting its potential in protection from harmful B[a]P-containing pollutants.